A Rare Case Series Of Sex Cord Stromal Cell Tumour - Meena, Meena; Jayanthi, Jayanthi; Bharathi, Bharathi; Prasanna, Prasanna (Journal of Neonatal Surgery, 2025)
Sex cord-stromal tumors (SCSTs) are a heterogeneous group of rare neoplasms arising from the sex cords and stromal components of the gonads, encompassing both the ovaries and testes. They account for approximately 5-8% of malignant potential is 3-4% of ovarian neoplasms and a smaller fraction of testicular tumors. These tumors are unique in that they often secrete sex steroids such as estrogen, progesterone, or androgens, contributing to diverse endocrine manifestations, including menstrual irregularities, virilization, or feminization depending on the hormone produced. Common subtypes include granulosa cell tumors, Sertoli-Leydig cell tumors, fibromas, and thecomas, each with varying clinical behavior and prognosis. While many SCSTs tend to follow a benign course, certain types exhibit malignant potential, necessitating long-term surveillance and intervention. Diagnosis is largely reliant on histopathological evaluation supported by immunohistochemistry, which helps differentiate them from other gonadal tumors. Imaging modalities such as ultrasound, CT, or MRI assist in initial localization and characterization but are not definitive. Treatment primarily involves surgical excision, often followed by adjuvant therapies like chemotherapy or radiotherapy, depending on factors such as histological subtype, tumor grade, and stage at presentation. Fertility-sparing surgery may be considered in younger patients with early-stage disease. Prognosis is generally favorable for benign tumors, but malignant variants may recur and require close follow-up. Advances in molecular genetics and biomarker discovery are contributing to improved diagnostic accuracy and individualized management strategies. Understanding the clinical, hormonal, and pathological spectrum of sex cord-stromal tumors is essential for timely diagnosis and optimal patient outcomes.